Legal Protection for Outsourced Workers/Laborers Towards Diploma Detention Policy Committed by The Employer (Journal of Governance Risk Management Compliance and Sustainability, 2023)
The massive development in business and the economy has provided new opportunities for the people in Indonesia, especially with the dream of improving careers and wages. However, at the same time, the recruiting system aiming to get the best workers is so complex that even it creates a new system called outsourcing. Unfortunately, this system has a few disadvantages for workers, especially concerning diploma detention cases. This study aims to analyze the legal protection for outsourced workers/laborers in Indonesia. This research uses the normative legal research method. The legal material secondary to this study is literature dealing with research problems. For processing the data, a conceptual approach and a statutory approach are used, and then descriptive research is used to produce a descriptive analysis. Although the issue of diploma detention is not commonly discussed in Indonesia, it can be said that the core of this problem is the minimum knowledge of the law and regulations. Thus, legal protection based on Indonesian Law and Regulation for the outsourced workers/laborers should be openly socialized to all outsourced workers/laborers. To limit the scope of this study, the analysis concerns to analyze the legal protection for outsourced workers/laborers in Indonesia based on the applicable law. The novelty of this research study is to provide a better idea and understand the possibility of criminal sanction for employers as one Legal Protection form for outsourced workers/laborers.